Deck‐stay interaction with appropriate initial shapes of cable‐stayed bridges. Issue 4 (2014) - Ming‐Yi Liu; Li‐Chin Lin; Pao‐Hsii Wang
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to provide a variety of viewpoints to illustrate the mechanism of the deck‐stay interaction with the appropriate initial shapes of cable‐stayed bridges, which is validated by a symmetrical structure. Design/methodology/approach – Based on the smooth and convergent bridge shapes obtained by the initial shape analysis, the one‐element cable system (OECS) and multi‐element cable system (MECS) models of the symmetric harp cable‐stayed bridge are developed to verify the applicability of the analytical model and numerical formulation from the field observations in the authors' previous work. For this purpose, the modal analyses of the two finite element models are conducted to calculate the natural frequency and normalized mode shape of the individual modes of the bridge. The modal coupling assessment is also performed to obtain the generalized mass ratios among the structural components for each mode of the bridge. Findings – The findings indicate that the coupled modes are attributed to the frequency loci veering and mode localization when the "pure" deck‐tower frequency and the "pure" stay cable frequency approach one another, implying that the mode shapes of such coupled modes are simply different from those of the deck‐tower system or stay cables alone. The distribution of the generalized mass ratios between the deck‐tower system and stay cables are useful indices for quantitatively assessing the degree of coupling for each mode. For each identical group of stay cables in the MECS model, the local modes with similar natural frequencies and normalized mode shapes consist of the participation of one or more stay cables. These results are demonstrated to fully understand the mechanism of the deck‐stay interaction with the appropriate initial shapes of cable‐stayed bridges. Originality/value – It is important to investigate the deck‐stay interaction with the appropriate initial shape of a cable‐stayed bridge. This is because such initial shape not only reasonably provides the geometric configuration as well as the prestress distribution of the bridge under the weight of the deck‐tower system and the pretension forces in the stay cables, but also definitely ensures the satisfaction of the relations for the equilibrium conditions, boundary conditions and architectural design requirements. However, few researchers have studied the deck‐stay interaction considering the initial shape effect. The objective of this paper is to fully understand the mechanism of the deck‐stay interaction with the appropriate initial shapes of cable‐stayed bridges, which is validated by a symmetrical structure. The modal coupling assessment is also performed for quantitatively assessing the degree of coupling for each mode of the bridge. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors would like to acknowledge the support of the National Science Council, Taiwan, under Grant No. NSC 101‐2221‐E‐033‐046. </ack>